2001
DOI: 10.1074/jbc.m009019200
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced Phosphoethanolamine Transfer to the Outer 3-Deoxy-d-manno-octulosonic Acid Moiety of Escherichia coli Lipopolysaccharide

Abstract: 32 P]lipid IV A , at pH 4.5 shows that the pEtN substituent is located on the outer Kdo moiety. Membranes from an E. coli pss knockout mutant grown on 50 mM CaCl 2 , which lack phosphatidylethanolamine, do not contain measurable transferase activity unless exogenous phosphatidylethanolamine is added back to the assay system. The induction of the pEtN transferase by 5-50 mM CaCl 2 suggests possible role(s) in establishing transformation competence or resisting environmental stress, and represents the first exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 29 publications
1
95
0
Order By: Relevance
“…In addition, LPS fractions which are releasable and non-releasable by EDTA should be studied for similar fine structures. In this context it is interesting to note the recent report of Kanipest et al (2001), who demonstrated in E. coli that the critical parameter determining the presence or absence of phosphoethanolamine was the CaCl 2 concentration in the medium. They observed a novel CaCl 2 -induced enzyme that modifies the outer Kdo moiety of E. coli LPS with a phosphoethanolamine group in the presence of 5-50 mM CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LPS fractions which are releasable and non-releasable by EDTA should be studied for similar fine structures. In this context it is interesting to note the recent report of Kanipest et al (2001), who demonstrated in E. coli that the critical parameter determining the presence or absence of phosphoethanolamine was the CaCl 2 concentration in the medium. They observed a novel CaCl 2 -induced enzyme that modifies the outer Kdo moiety of E. coli LPS with a phosphoethanolamine group in the presence of 5-50 mM CaCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a pEtN unit to the outer Kdo residue by EptB (Fig. 1) is independent of PmrA/PmrB and PhoP/ PhoQ, but instead is induced by 5 to 50 mM Ca 2+ ions (22,23).…”
Section: Introductionmentioning
confidence: 99%
“…The Kdo 2 -lipid A species (unresolved substrate and hydroxylated product) were re-purified from the crude reaction mixture by Bligh/Dyer extraction followed by anion-exchange chromatography on DEAE cellulose (22). The Kdo 2 -lipid A species were then analyzed directly without pH 4.5 hydrolysis by negative ion ESI/MS (Fig.…”
Section: Esi/ms Of the Product Generated By Lpxo-catalyzed Hydroxylatmentioning
confidence: 99%
See 2 more Smart Citations